Analysis of variance dimension of reinforcement to stress concentration factor using Finite Element Method - Ali Ali; Diki Ismail Permana; Hermawan Nurfakhira Yudha (Universitas Mercu Buana, 2022)
Stress concentration is a condition when stress increases only at a certain area of a component compared to the stress at the uniform cross-section of the component when given a load. This phenomenon can occur due to irregular geometry such as a hole, sharp angle, cross-section change, notch, threads, groove, crack, etc. Any change in geometric shape on a uniform cross section will cause a stress increases. High stress concentrations need to be reduced to prevent faster failure of a component. The stress concentration that occurs can be determined by using stress concentration factors (Kt). Using FEM method, the simulation obtained stress distribution that occurs in the shaft that is modelled, both without and with the additional groove. The results obtained by the additional of a semi-circular groove can reduce stress concentrations up to ten percent.